Применение методики создания теста в компьютерных системах дистанционного обучения - Хапров, B. C.; Дударь, З. В. (УАДО, 2002)
The article is dedicated to the problem of knowledge acquisition quality control in distance education systems. The research is targeted at development of recommendations on test design and interpretation of knowledge testing results. The goal in view is achieved by means of successive solving of a series of procedure-development tasks selecting test assignments; evaluating test reliability; evaluating test validity by independent exterior criterion; evaluating accuracy and reliability of test results. A program system realizing designed procedures has been developed.
Keywords: дистанционное образование